The Effectiveness of Emotion Schema Therapy on Rumination and the Extreme Accountability of Patients with Obsessive-Compulsive Disorder - Atefeh Ghovati (Alzahra University, 2021)
Due to the prevalence of obsessive-compulsive symptoms, there are some measures to be taken to improve the symptoms. The purpose of the present research was to determine the effectiveness of emotion schema therapy on rumination and the extreme accountability of patients with obsessive-compulsive disorder. It was semi-experimental research with pre-test, post-test, and follow-up stage. The population of the study included people with obsessive-compulsive disorder who referred to the Artiman counseling center of Mashhad in 2019. A number of 16 individuals were selected by available sampling and they were divided randomly into two experimental and control groups. The Ruminant Response Style Questionnaire and California Accountability Scale were used to collect data. The results of analysis of variance with repeated measures showed that emotion schema therapy effects on reducing rumination and extreme accountability of individuals with obsessive-compulsive disorder. Emotional schema therapy can be effective in reducing mental rumination and extreme accountability of people with obsessive-compulsive disorder. It is suggested that by using these variables by medical centers, the organizations can be taken to take effective steps to improve the mental health of individuals